Enhancing Maternal and Reproductive Health through Multidisciplinary Collaboration: The Role of Nurses, Pharmacists, Medical Consultants, and Gynecologists - Dr.Sultan Yahya Mohammad Alfaife,; Yazeed Hussain Mohammad aljimaee,; Ebtehal Hussein Aljumaai,; Ashwaq Mushabab Assiri,; Mohammed Mufarh Mohammed Alqahtani,; Eman Muneis Mons Alghamdi,; Fahad Mohammad Braik Almowallad,; Ahmed Ali Mohammed Asseri,; Norah I. Almanie, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Improving maternal and reproductive health is one of the critical areas in the health agenda globally. This field is quite broad because it considered different issues like maternal death, reproductive health, perinatal care and reproductive services. Management of these challenges thus needs a collaborative model of care delivery at which different categories of healthcare professionals provide patients with coordinated and integrated care. Nurses, pharmacists, medical consultants and gynecologists are able to coordinate their efforts to enhance maternal and reproductive health of women. Aim of work: To provide a comprehensive understanding of the role of nurses, pharmacists, medical consultants, and gynecologists inenhancing maternal and reproductive health through multidisciplinary collaboration Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Role Nurses, Pharmacists, Medical Consultants, Gynecologists, Enhancing Maternal, Reproductive Health, Multidisciplinary, Collaboration. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:In conclusion, the improvement of maternal and reproductive health by a comprehensive intervention strategy keeps vigilance on advanced health issues in this domain. A strong and patient protective collaboration is provided by nurses, pharmacists, medical consultants, and gynecologists each of whom offers special competencies to the framework in order to provide women with individualized safe and evidence based care. Quite predictably, as the global focus shifts to some other health threats, the interdisciplinary cooperation will remain the essential prerequisite to enhancing the outcomes for maternal and reproductive health.